THE ISLAMIC BEHAVIOR IMPACT FOR ECONOMIC DEVELOPMENT AND MACROPRUDENTIAL POLICY - Kawilujengan, Rasul TH; Mukhsin, Moh. (Cahaya Ilmu Bangsa, 2024)
This study explores the impact of Islamic behavior on economic development and macroprudential policy, with a focus on the integration of sharia principles to achieve inclusive financial stability. The goal is to analyze the influence of Islamic behavior, transmit macroprudential policies in Islamic economics, and provide recommendations for more effective and equitable development. This study uses a combination of qualitative and quantitative approaches to explore the impact of Islamic behavior on economic development and macroprudential policies. Data is collected through in-depth interviews, surveys, and case studies. The analysis includes thematic techniques for qualitative data and statistical analysis for quantitative data, in order to provide in-depth understanding and data-driven recommendations. Research has found that sharia principles, such as zakat and the prohibition of usury, are effective in redistributing wealth and improving social welfare. Macroprudential policies need to be adjusted to sharia principles, including profit-sharing-based financing and strict supervision of Islamic financial institutions. The implementation of sharia principles in fiscal and monetary policy supports the equitable distribution of wealth and economic stability. This study shows that Islamic behavior is positive for economic development and that macroprudential policies can be adjusted to sharia principles to improve social welfare and economic stability. The recommendations include the integration of sharia principles in policy, strengthening sharia economic infrastructure, increasing literacy, and collaboration between sectors to support sustainable sharia economic growth.